2017
DOI: 10.1111/cobi.13007
|View full text |Cite
|
Sign up to set email alerts
|

Long‐distance flights and high‐risk breeding by nomadic waterbirds on desert salt lakes

Abstract: Palabras Clave: ave acuática, ave costera, desierto, especie móvil, nomadismo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Most environments, however, are neither entirely consistent nor entirely predictable, which can affect the consistency with which individuals are able to perform their migrations (e.g., Studds and Marra, 2011). In addition, an individual can exhibit different migration strategies with increasing experience (e.g., individual improvement; Sergio et al, 2014), because the environment requires flexibility (e.g., nomadism ;Pedler et al, 2018), or because the environment allows flexibility (e.g., the absence of carry-over effects; Senner et al, 2014). Differences in an individual's migratory behavior across years (i.e., intra-individual variation) therefore also contribute to migration variation at the population level (sensu Conklin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Most environments, however, are neither entirely consistent nor entirely predictable, which can affect the consistency with which individuals are able to perform their migrations (e.g., Studds and Marra, 2011). In addition, an individual can exhibit different migration strategies with increasing experience (e.g., individual improvement; Sergio et al, 2014), because the environment requires flexibility (e.g., nomadism ;Pedler et al, 2018), or because the environment allows flexibility (e.g., the absence of carry-over effects; Senner et al, 2014). Differences in an individual's migratory behavior across years (i.e., intra-individual variation) therefore also contribute to migration variation at the population level (sensu Conklin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, individuals may vary their departure dates from non-breeding sites by as little as 3 days over 4 consecutive years (Conklin et al, 2013). In contrast, other studies have found that individuals of some species can exhibit marked improvement and flexibility in their migratory timing and performance, enabling them to adjust their behaviors to prevailing environmental conditions (Sergio et al, 2014;Pedler et al, 2018). What remains unclear, though, is how flexible migratory behaviors are generally and how both historical and contemporary selection pressures may mold the levels of flexibility exhibited by individuals within a population.…”
Section: Introductionmentioning
confidence: 99%
“…The high unexplained variances for the radjah shelduck, magpie goose and plumed whistling duck are likely caused by the latter, as their typical range straddles the northern boundary of EAWS survey area, with greater movement into the survey area on occasion in response to seasonal conditions. Likewise, recent studies suggest that the entire population of banded stilt can move into and out of the survey region (Pedler et al 2014(Pedler et al , 2018, which explains the high year-to-year variation in φ, including very low (and sometimes zero) counts in some years (particularly during the Millennium Drought: see Fig. 5c and Fig.…”
Section: On Explaining Variationmentioning
confidence: 80%